Discipline in School, Gender and Sexuality: Practices and Punishment production of identity - Salum Moreira, Maria de Fátima; Piorkowsky dos Santos, Lilian (Education Policy Analysis Archives, 2004)
This paper presents the results of a research where the phenomenon of indiscipline was problematized approaching its possible relationship with the production of gender identities, in and through school. By means of interviews and direct observation, in classes of the 8th grade of a school was carried out a study about the (male and female) teachers? attitudes towards what they consider their pupils? indiscipline (which are teenagers, about 13 / 14 years old). At the same time it was made an analysis about the practices of school punishment, threreby a listing of the punishments imposed to "desobedient" students? behavior. This listing came out from consultation to the " book of disciplinary records of the students". So it was possible to bring about, among others, some important aspects of this process: a) the coherence (or incoherence) between what teachers consider "indiscipline" and their actual practices and attitudes towards students? behavior; b) The diferences and analogies among (male and female) teachers?practices and attitudes c) The different ways in which teachers deal with the manifestations of gender and sexuality of the (male and female) students, at the same time associate them to the practices of insubordination and indiscipline; d) the production of identities, distinctions and inequalities of gender and sexuality, thru school practices.